Chinese History and Literature : Collection of Studies - Průšek, Jaroslav (Dordrecht : Springer Netherlands : Imprint: Springer, 1970., 2017)
Ancient Literature. Literature oj the Ok'ing Period. Folklore -- Medieval Popular Literature --